Analysis of the Sensory Processing Profile of Students with Autistic Spectrum Disorder and its Influence on School Participation (Global Journal of Medical Research, 2023)
casos, o transtorno do déficit de atenção, em 30%, a depressão, em 2 a 30%, a ansiedade, de 5 a 45 %, a epilepsia, de 7 a 46% dos casos (SIMONOFF et al.,